DAMPAK PEMBERLAKUAN SISTEM ZONASI TERHADAP MUTU SEKOLAH DAN PESERTA DIDIK - Riski Tri Widyastuti (STKIP PGRI Situbondo, 2020)
Education is a conscious and planned effort to shape civilized people. Education is very important for a nation that national development can work well and corresponding maximum Pancasila and the 1945 Constitution. In education there is a system called Education is a conscious and planned effort to shape civilized people. Education is very important for a nation so that national development can run well and maximally in accordance with Pancasila and the 1945 Constitution. In education there is a system called the education system. Today education in Indonesia uses a zoning system in the acceptance of new students, the zoning system is implemented with the hope that the realization of educational equality in various regions. During this time what happened in Indonesia is the emergence of the title of 'favorite school' in schools that are considered to have high achievements so that this 'favorite school' usually becomes the target of parents and students so concentration occurs. This causes schools that are considered not favorite to be short of students, besides that, the differences between favorite and non-favorite schools cause intolerant attitudes among students which are not in accordance with the values of Pancasila. Zoning itself is the acceptance of new students by looking at the closest distance from school to home with a minimum quota of 90% of the total prospective students received. The impact of this zoning varies both positive and negative both on the quality of the school and on students themselves..